Manganese(II), Iron(II), Cobalt(II), Nickel(II) and Zinc(II) Complexes of 2-(N-Salicylideneamino)-3-Carboxyethyl-4,5,6,7-Tetrahydrobenzothiophene - Nirmala Devi, S.; Mohanan, K. (Asian Journal of Chemistry, 2010)
Condensation of 2-amino-3-carboxyethyl-4,5,6,7-tetrahydrobenzothiophene with salicylaldehyde gives a potentially tridentate Schiff base, viz., 2-(N-salicylideneamino)-3-carboxyethyl-4,5,6,7-tetrahydrobenzothiophene (HSAT). This Schiff base froms well defined metal complexes, with manganese(II), iron(II), cobalt(II), nickel(II) and zinc(II) ions. The complexes have been characterised by elemental analytical, molar conductance, magnetic susceptibility, UV, IR and NMR spectral data. The spectral studies reveal that the ligand moiety is bonded to the metal ion through the deprotonated phenolate oxygen, azomethine nitrogen and ester carbonyl. Manganese(II), iron(II) and cobalt(II) complexes exhibit 1 : 2 metal-ligand ratio; while nickel(II) and zinc(II) complexes show 1 : 1 ratio.